2014
DOI: 10.1186/1471-2458-14-32
|View full text |Cite
|
Sign up to set email alerts
|

The Be Our Ally Beat Smoking (BOABS) study, a randomised controlled trial of an intensive smoking cessation intervention in a remote aboriginal Australian health care setting

Abstract: BackgroundAustralian Aboriginal and Torres Strait Islander peoples (Indigenous Australians) smoke at much higher rates than non-Indigenous people and smoking is an important contributor to increased disease, hospital admissions and deaths in Indigenous Australian populations. Smoking cessation programs in Australia have not had the same impact on Indigenous smokers as on non-Indigenous smokers. This paper describes the outcome of a study that aimed to test the efficacy of a locally-tailored, intensive, multidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 25 publications
(34 reference statements)
2
56
0
1
Order By: Relevance
“…A meta‐analysis of two randomised controlled trials showed intensive cessation counselling programs for Aboriginal and Torres Strait Islander smokers were effective in increasing cessation 26 . We found that most people who attended special cessation programs said they were specifically designed for Aboriginal and Torres Strait Islander peoples.…”
Section: Discussionsupporting
confidence: 51%
“…A meta‐analysis of two randomised controlled trials showed intensive cessation counselling programs for Aboriginal and Torres Strait Islander smokers were effective in increasing cessation 26 . We found that most people who attended special cessation programs said they were specifically designed for Aboriginal and Torres Strait Islander peoples.…”
Section: Discussionsupporting
confidence: 51%
“…Outcomes in context: Summarised and highlighted in Table , none of the evaluations of implementation reported statistically significant effects attributable to the intervention 22–24 . However, meta‐analysis of the pooled data from two (A1 and A2) found a significant effect of intensive health worker support on tobacco cessation 24 . Program A1 established that pregnant women who had already quit smoking independently of an intervention remained non‐smokers at the end of their pregnancy 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, none of the studies were able to demonstrate a large or socially significant reduction in levels of use of the targeted substance, nor a clear effect attributable to the intervention. Low fidelity of implementation, 30 weak study designs 36 and inevitably small sample sizes 24 undermined the utility of the results of most studies.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental designs such as these are only possible when considered during program development and implementation, and if relevant to and supported by participating communities. Such evaluations may not be appropriate or required in every setting, particularly in the case of complex public health interventions or when the evaluation is conducted with a small sample or in one setting, but as they provide a high level of evidence, they must be given due consideration during program design 12 . Calls for their use must also be based on an assessment of their utility, feasibility, and value to service agencies and communities during program planning.…”
Section: Discussionmentioning
confidence: 99%